Genesis of Vajrayāna Caryāgītimanjari: A Newā Buddhist Literature - Shrestha, Arun (SIRJANĀ – A Journal Of Arts and Art Education, 2025)
Caryāgītimanjarī is an abstraction of Vajrayāna philosophy or an upaniśada of Vajrayāna Buddhism. It is a gist of Vajrayāna philosophy and its doctrine or a āgama veda – a divine religious text of wisdom. These caryāgīti bring to life the sacred scripture (āgama), a sacred knowledge (veda) of ancient time (purāṇa) and it is described (bakhāne) in caryāgīti. It is rightly said so on caryāgīti: āgama veda purāņa bakhāne 2 yoga dharma dīkśā gurupadeśa II dhu II The glory of caryāgīti is expressed in the stanza: The one called great pleasure (mahāsukha) has arisen, protects by virtue of the song (gīta) and dances (nrityatu). jātā eka mahāsukha nāmā 2 nŗtyantu gīta balena rakşena II II And to sum it up, an ultimate obeisance is paid to caryāgīti emphasizing the prominence of kāya (body), vāka (speech) and citta (mind): ākāśakāyasambhūta ākāśavākapravartaka I ākāśachittadharmāgra caryāpada namohstu te II II Caryāgīti commands a place of pride in art, culture, religion and literature of Newā community.